Transformational model of textual activity: critical realism and critical discourse analysis - Barros, de Solange Maria (Romanica Olomucensia, 2015)
In this paper, the Transformational Model of Textual Activity (TMTA), based on critical discourse analysis and critical realism, is presented. According to the TMTA, society exists by virtue of individuals who can reproduce it and modify it through language. The use of language (oral or written) can bring about changes in our knowledge, in our beliefs, etc. Fairclough argues that texts can start wars and contribute to changing the material world, industrial relations, education, and so on. Individuals produce texts and these are parts of social events which are shaped by the causal powers of social structures. Considering that texts are parts of social life with its mechanisms and causal powers, they have been structured in a "laminate system" or rolled circles and organized into a hierarchy ranging from a macro scale to a micro scale, which are: global, macrosocial interaction, microsocial interaction, individual, and sub-individual, these being dialectically related. The paper is divided into three sections. Initially, the philosophy of critical realism proposed by Bhaskar and Fairclough's approach is presented. The identificational meaning category associated with the concept of style is investigated. The Transformational Model of Textual Activity (TMTA) is explained, with one of these systems being applied in a practical classroom activity. Finally, the paper endeavours to reflect on critical language education in the sense of achieving a more human and united world.
Keywords: TMTA; critical realism; critical discourse analysis; critical education.